Picotamide inhibits a wide spectrum of agonist‐induced smooth muscle contractions in porcine renal interlobar and coronary arteries - Bingsheng Li; Ru Huang; Ruixiao Wang; Yuhan Liu; Christian G. Stief; Martin Hennenberg (Wiley, 2021)
Abstract Picotamide is a thromboxane A2 (TXA2) receptor antagonist and TXA2 synthase inhibitor. In clinical studies, it has been considered as a platelet aggregation inhibitor and improved renal function. In vitro studies suggested inhibition of smooth muscle contraction by picotamide, which is poorly understood. Here, we examined effects of picotamide on contractions of renal interlobar and coronary porcine arteries, induced by different vasoconstrictors. Contractions were induced in an organ bath by agonists or electric field stimulation (EFS). Picotamide inhibited EFS‐induced contractions of interlobar arteries around 50% using concentrations of 100 and 300 µM. In interlobar arteries, concentration response curves for contractions induced by three different α1‐adrenoceptor agonists were shifted to the right by picotamide (2-10‐fold increases in EC50). In coronary arteries, α1‐adrenergic contractions were inhibited without right shift (approx. 50%). Contractions induced by two different cholinergic agonists in coronary arteries were inhibited by picotamide (≥50%) withouth right shift. Inhibition of serotonin‐induced contractions by picotamide showed features of a right shift, whereas contractions induced by the TXA2 analog U46619, angiotensin‐II, and endothelin‐1 were inhibited by picotamide in interlobar and coronary arteries without right shifts and to different degree. Picotamide inhibits a wide spectrum of vasoconstrictor‐induced contractions in porcine interlobar and coronary arteries. Inhibition of vasocontraction may contribute to beneficial effects of picotamide in the cardiovascular system and kidney.